Design of Novel Compact Tri-Band Bandpass Filter Using Embedded Resonators. Issue 3 (3rd April 2019) - Liu, Hui; Zhang, Luokai; Li, Junlong; Luo, Miaohui; Gao, Li
ABSTRACT: A novel compact tri-band bandpass filter is presented in this article. The proposed circuit utilizes a second-order embedded resonator. By controlling different parts of the embedded resonator, the operating frequencies can be controlled individually. Furthermore, by introducing source-load coupling, transmission zeros are generated near the passband, resulting in high selectivity. To verify the proposed idea, a tri-band bandpass filter with operating frequencies of 2.4/3.5/5.15 GHz is implemented, which are used to cover the WiFi and WiMax system. The design procedures are discussed in detail, and the simulated and measured results are presented.